A Defense of Intrapersonal Belief Permissivism. (11th June 2021) - Jackson, Elizabeth
Abstract: Permissivism is the view that there are evidential situations that rationally permit more than one attitude toward a proposition. In this paper, I argue for Intrapersonal Belief Permissivism (IaBP): that there are evidential situations in which a single agent can rationally adopt more than one belief-attitude toward a proposition. I give two positive arguments for IaBP; the first involves epistemic supererogation and the second involves doubt. Then, I show how these arguments give intrapersonal permissivists a distinct response to the toggling objection. I conclude that IaBP is a view that philosophers should take seriously.